If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(x + 4) = 5x + 57 Reorder the terms: 7(4 + x) = 5x + 57 (4 * 7 + x * 7) = 5x + 57 (28 + 7x) = 5x + 57 Reorder the terms: 28 + 7x = 57 + 5x Solving 28 + 7x = 57 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 28 + 7x + -5x = 57 + 5x + -5x Combine like terms: 7x + -5x = 2x 28 + 2x = 57 + 5x + -5x Combine like terms: 5x + -5x = 0 28 + 2x = 57 + 0 28 + 2x = 57 Add '-28' to each side of the equation. 28 + -28 + 2x = 57 + -28 Combine like terms: 28 + -28 = 0 0 + 2x = 57 + -28 2x = 57 + -28 Combine like terms: 57 + -28 = 29 2x = 29 Divide each side by '2'. x = 14.5 Simplifying x = 14.5
| x/2-7x=8 | | 10-7x=-88 | | 3-7x=-53 | | y=0.39x+200 | | 6x+4=94 | | 12-5x=-33 | | 5-7x=-51 | | -k^2-65k+720=0 | | 5+8x=53 | | 50x+(25)(799x)=2.5 | | 2x+2x+4+x^2= | | 15=4x-19 | | 6(5z-1)-2(z+1)=3(z+1) | | 6x+8=3x-19 | | 3+8x=13-2x | | 16d+1=9d+15 | | y+2x=-18 | | 125x^3/343 | | 6(5z-1)-2(z+5)=7(z+1) | | 2(x-5)=-9.2 | | 8.1=3c-9 | | -4(t-3)-(t+3)=2 | | 6e-2=54.4 | | 8(x-9)=-32 | | 3(a+7)=48 | | 28=8c-4 | | 7+8(x-7)=4-6(x-4) | | 5e-4=21 | | 5z(z-3)(z+6)=0 | | (1-w)(5w+3)=0 | | -3(x^3)+23(x^2)+24x+52=0 | | 36+4y=-8y |